Interlinking Leukemia Cell Lines with Clinicopathological Therapeutics: Exploring Eugenol’s Anti-Cancer Potential for Leukemia and Its Types: Exploring Eugenol’s Anti-Cancer Potential for Leukemia and Its Types - Wadood, Maeesa; Zafar, Shahid; Anwar, Bushra; Bhatti, Maira; Ali, Shahid; Niaz, Mahwish; Ali, Muhammad Akram (Pakistan Journal of Health Sciences, 2024)
The clove oil contains a bioactive compound, eugenol, which holds promise as a therapeutic agent in cancer treatment, such as leukemia. Objectives: To represent eugenol’s clinicopathological potential, through the mechanism of action in leukemia cell lines and related mechanisms. Methods: Eugenol's anti-cancer effects are explored through pathways of apoptosis induction, cell cycle regulation and modulation of key oncogenic signalling pathways, including nuclear factor-kappa B, signal transducer and activator of transcription 3 and phosphatidylinositol 3-kinase/protein kinase B. One hundred twelve articles including those published between January 2013 to April 2024 were obtained using a comprehensive search after a conduction of a comprehensive search as directed by the PRISMA guidelines using databases such as PubMed, Google Scholar and, Semantic Scholar. Fifty-six studies that fulfilled the inclusion criteria were screened after which 42 studies on eugenol’s therapeutic effects in leukemia cells were found. 15 studies were finally included in the review table Results: It is found to induce reactive oxygen species and to inhibit tumor proliferation, as well as to improve the efficacy of conventional chemotherapeutics, according to research. The selective toxicity of eugenol toward leukemic cells with minimal effect on healthy peripheral blood cells is thus particularly appealing as a basis for use in the clinic. Furthermore, in vitro, in vivo and silico experiments show that eugenol, in combination with current cancer treatments, would better promote therapeutic outcomes. Conclusions: It was concluded that eugenol represents a novel therapeutic direction in leukemia and thus offers a compelling candidate for future drug development.